Comparative Effectiveness of 2 Interventions for Hispanic Caregivers of Persons with Dementia. Issue 9 (7th August 2018) - Luchsinger, José A.; Burgio, Louis; Mittelman, Mary; Dunner, Ilana; Levine, Jed A.; Hoyos, Carolina; Tipiani, Dante; Henriquez, Yefrenia; Kong, Jian; Silver, Stephanie; Ramirez, Mildred; Teresi, Jeanne A.
Abstract : Objectives: To compare the effectiveness of 2 caregiver interventions with known efficacy: the Resources for Enhancing Caregiver Health‐Offering Useful Treatment (REACH‐OUT) and the New York University Caregiver Intervention (NYUCI). Design: 1:1 randomized pragmatic trial. Setting: New York City. Participants: Informal Hispanic caregivers of persons with dementia (N=221; mean age 58.2, 82.8% female, 63.3% adult children, 31.7% spouses). Intervention: Participants were randomized to 6 months of NYUCI (n=110) or REACH‐OUT (n=111), balanced on characteristics at baseline. All participants were referred for social supportive services. Measurements: The primary outcomes were changes between baseline and 6 months in depressive symptoms, measured using the Geriatric Depression Scale (GDS), and caregiver burden, measured using the Zarit Caregiver Burden Scale (ZCBS). Results: There were no differences in outcomes between NYUCI and REACH‐OUT. Both interventions showed a reduction in burden (REACH‐OUT: 5.2 points, 95% confidence interval (CI)=2.2–8.1, p<.001; NYUCI: 4.6‐points, 95% CI=1.7–7.5, p=.002). There were no significant changes on the GDS. Effects for the ZCBS were significant only for spouses and older caregivers. Conclusion: Although there were no significant intervention group differences, both interventions resulted in significantly reduced burden for Hispanic caregivers at 6 months, particularly for spouses and older caregivers.